The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acs.cgd.8b00648
|View full text |Cite
|
Sign up to set email alerts
|

Exposing Key Vibrational Contributions to Properties of Organic Molecular Solids with High Signal, Low Frequency Neutron Spectroscopy and Ab Initio Simulations

Abstract: Stability and response of supramolecular forms is important to many areas in materials science, and contributions from vibrations can be crucial. We have collected the first spectra of organic molecular crystals and polymorphic cocrystals using the next-generation, high-signal VISION spectrometer in the far-infrared (FIR) and mid-infrared (MIR) range. Unambiguously different spectral signatures were found for carbamazepine and two polymorphs of the carbamazepine-saccharin cocrystal, including numerous modes un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…normal mode decomposition into local mode contributions and the relation of normal modes to local modes with the help of an adiabatic connection scheme, which has been successfully applied to molecular systems . With the emerging number of experimental as well as theoretical studies on IR and Raman spectra of crystalline materials, , this project is more than timely.…”
Section: Discussionmentioning
confidence: 99%
“…normal mode decomposition into local mode contributions and the relation of normal modes to local modes with the help of an adiabatic connection scheme, which has been successfully applied to molecular systems . With the emerging number of experimental as well as theoretical studies on IR and Raman spectra of crystalline materials, , this project is more than timely.…”
Section: Discussionmentioning
confidence: 99%
“…The intensity of an inelastic neutron scattering (INS) band is given by ,, where σ l is the scattering cross-section of atom l , u l ,ν is the atomic displacement amplitude of the atom l in a mode ν , and ω ν is the frequency of that mode. Q is the magnitude of momentum transfer and n is the order of vibrational excitation.…”
Section: Methodsmentioning
confidence: 99%
“…Inelastic neutron scattering (INS) spectroscopy is a useful tool to probe hydrogen motions in the hydrogen containing systems and has a simple theoretical description, which can be simulated from the normal modes obtained by the lattice dynamics calculation under the harmonic approximation. , Recently, we have shown that these normal modes are sensitive to the functional used in the calculation and must be carefully benchmarked for the accurate spectral assignment . To study the thermodynamic properties at finite temperature and pressure and to improve the spectral prediction, the partial anharmonic effect can be incorporated within the quasi-harmonic approximation (QHA). , Barrera et al and Yu et als have shown the inadequacy of static approximation and the importance of finite-temperature effect in the thermodynamic properties of alkali-metal hydrides.…”
Section: Introductionmentioning
confidence: 99%